Bark Effects on Stemflow Chemistry in a Japanese Temperate Forest II. The Role of Bark Anatomical Features - Oka, Ayano; Takahashi, Junko; Endoh, Yoshikazu; Seino, Tatsuyuki (Frontiers in Forests and Global Change, 2021)
A fraction of rainfall drains to the soil surface down tree stems (as “stemflow”), and the resulting stemflow waters can be highly enriched with dissolved nutrients due to prolonged bark contact. To date, stemflow chemistry has been examined mostly in regards to the external morphology of the bark, while its relationship with bark anatomy has received little attention. Arguably, this represents a major knowledge gap, because bark anatomical traits are linked to the storage and transport of soluble (and insoluble) organic materials, and control the proximity of these materials to passing stemflow waters. To initiate this line of investigation, here, we examine bark-water leaching rates for common leachable macronutrient ions (Mg2+, Ca2+, and K+) across six different tree species with varying bark anatomical traits (four deciduous broadleaved and two evergreen coniferous species). These different bark types were subjected to laboratory experiments, including observations of bark anatomy and soaking experiments. Laboratory-derived estimates of leaching rates for Mg2+, Ca2+, and K+ were then analyzed alongside bark anatomical traits. Leaching rates of Mg2+ and Ca2+ appear to be controlled by the thickness of the rhytidome and periderm; while K+ leaching rates appeared to be driven by the presence of cellular structures associated with resource storage (parenchyma) and transfer (sieve cells). Other species-specific results are also identified and discussed. These results suggest that the anatomical features of bark and the concentration of leachable macronutrient ions in stemflow are related, and that these relationships may be important to understand nutrient cycle through the bark. We also conclude that future work on the mechanisms underlying stemflow solute enrichment should consider bark anatomy.